2009
DOI: 10.1017/s0033291709990948
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of cognitive biases in patients with current depression and remitted depression and in patients with asthma

Abstract: Background-Previous studies have demonstrated a specific cognitive bias for sad stimuli in currently depressed patients; little is known, however, about whether this bias persists after recovery from the depressive episode. Depression is frequently observed in patients with asthma and is associated with a worse course of the disease. Given these high rates of co-morbidity, we could expect to observe a similar bias towards sad stimuli in patients with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
116
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(142 citation statements)
references
References 56 publications
20
116
2
4
Order By: Relevance
“…Moreover, these distorted cognitive processes can be found in at-risk (Dearing & Gotlib, 2009;Joormann, Talbot, & Gotlib, 2007;Kujawa et al, 2011;Taylor & Ingram, 1999) and remitted (Fritzsche et al, 2010;Gilboa & Gotlib, 1997;Hedlund & Rude, 1995;, 2010 depressed samples.…”
Section: Cognitive Biases and Vulnerability For Depressionmentioning
confidence: 99%
“…Moreover, these distorted cognitive processes can be found in at-risk (Dearing & Gotlib, 2009;Joormann, Talbot, & Gotlib, 2007;Kujawa et al, 2011;Taylor & Ingram, 1999) and remitted (Fritzsche et al, 2010;Gilboa & Gotlib, 1997;Hedlund & Rude, 1995;, 2010 depressed samples.…”
Section: Cognitive Biases and Vulnerability For Depressionmentioning
confidence: 99%
“…127,129,[134][135][136][137][138][139][140][141][142] Enhanced recognition of sad facial expressions has also been consistently reported in acutely depressed patients. 73,[143][144][145][146][147][148] Other studies have reported evidence of a negative bias during facial expression recognition and detection tasks, 138,140,[149][150][151][152][153][154][155][156] including a tendency to identify neutral faces as sad in patients with moderate to severe depressive symptoms compared with healthy controls. [157][158][159] This bias is accompanied by selective attention to negatively valenced faces depicting sadness 134,147,155,160 and anger.…”
mentioning
confidence: 99%
“…Elliot et al, 2011;Farb et al, 2011;Fritzsche et al, 2010), a dosadaÅ”nji nalazi ukazuju na značajnu prediktivnu moć specifičnih obrazaca ove mreže u predviđanju depresivne epizode (Marchetti et al, 2013). Međutim, uprkos povećanom interesu za ispitivanje moždanih aktivnosti tokom mirovanja koristeći tehnike neuroodslikavanja, neophodna je i dalja provera neuralnih korelata kognitivnih faktora vulnerabilnosti koristeći bihejvioralne metode paradigme mirovanja, kako na uzorcima vulnerabilnih osoba, tako i na kliničkim uzorcima.…”
Section: Diskusijaunclassified
“…Pretpostavlja se da su ove mentalne aktivnosti povezane sa neuronskom mrežom mirovanja (engl. default mode network) koja je aktivna kada osoba nije fokusirana na zbivanja u spoljaÅ”njoj sredini, već je fokusirana na misli o sebi, priseća se događaja iz proÅ”losti, zamiÅ”lja moguće buduće situacije ili joj "misli lutaju" (Chen et al, 2013;Elliot, Zahn, Deakin, & Anderson, 2011;Farb, Anderson, Bloch, & Segal, 2011;Fritzsche et al, 2010;Reichle & Snyder, 2007). Neuronska mreža mirovanja je jedna od tri velike neuralne mreže za koje se pretpostavlja da međusobnim delovanjem u velikoj meri učestvuju u obradi informacija tokom emocionalnih i kognitivnih procesa (Chen et al, 2013).…”
unclassified